Exploring the contribution of integrated healthcare practices to malaria control in Ghana: perspectives of medical herbalists - Irene G. Ampomah; Susan Devine; Genevieve A. Ampomah; Theophilus I. Emeto (BMC Complementary Medicine and Therapies)
Abstract Background The integration of herbal and orthodox medicines has gained momentum in global health, ensuring improved management of infectious diseases like malaria. This study explored the experiences of medical herbalists working in Ghana’s diverse ecological zones to understand the contributions of integrated healthcare to malaria control. Methods A phenomenological design was employed to conduct in-depth interviews with 19 purposively sampled medical herbalists. Framework analytical approach and Donabedian’s conceptual framework for quality of care were utilised in analysing the data. Results Findings revealed high awareness of integrated healthcare practices among participants. Medical herbalists perceived integrated care as instrumental in enhancing malaria management through factors such as improved quality assurance, increased accessibility to integrated health facilities, patient-centred care, follow-up practices, and opportunities for continuous professional development. However, structural and process-related challenges were identified, including inadequate healthcare personnel, medicines, and equipment. Additionally, limited promotional activities, non-comprehensive National Health Insurance Scheme (NHIS), and ineffective referral systems were recognised as barriers hindering the effectiveness of the integrated system and its potential contribution to malaria control. Conclusion Although national and health system-based challenges have thwarted the importance of integration on malaria control, medical herbalists feel optimistic about the intervention. To optimise the effectiveness of integrated healthcare in controlling malaria in Ghana would require policy modification and implementation. Future research could focus on developing healthcare frameworks, particularly for malaria, that prioritise quality service delivery within an integrated system.